Role of Vitamin D on glycemic control and oxidative stress in type 2 diabetes mellitus - Saif-Elnasr, Mostafa (J Res Med Sci, 2017)
BACKGROUND: Vitamin D deficiency may play a key role in the development of impaired glucose tolerance, type 2 diabetes mellitus (T2DM), and metabolic syndrome. Several studies have shown that Vitamin D has an antioxidant property. We aimed to investigate 25-hydroxy Vitamin D (25[OH]D) levels in patients with T2DM and in nondiabetic healthy controls and to ascertain the impact of 25(OH)D levels on glycemic control and oxidative stress in T2DM patients. MATERIALS AND METHODS: Thirty male patients with T2DM and twenty age- and socioeconomic status-matched male healthy controls were included in the study. Fasting and postprandial blood sugar and glycated hemoglobin (HbA1c) were measured. Enzyme activity of superoxide dismutase (SOD) and glutathione peroxidase (GPx) was determined by spectrophotometric assay, and serum levels of 25(OH)D were measured using radioimmunoassay. RESULTS: Serum Vitamin D levels were significantly lower in patients with T2DM than healthy controls (P = 0.015). There was a significantly lower GPx activity in patients with T2DM than controls (P = 0.048), but the difference in SOD activity did not reach statistical significance. There was a significant negative correlation between serum Vitamin D levels and HbA1c (P = 0.016), but no statistical correlation was shown between serum Vitamin D levels and GPx and SOD. CONCLUSION: We conclude that low level of Vitamin D might play a significant role in T2DM pathogenesis. Hence, Vitamin D supplementation may improve glycemic control and oxidative stress in T2DM.